The Impact of Implementing Formal HRM Practices on Small Firm Dynamics, Employee Motivation and Performance in Tourism and Hospitality Industry in Mallorca - Szymanska, Patrycja (Digital Repository of Theses, 2026)
Formalization of Human Resource Management (HRM) practices is an important component of contemporary HRM. Formalized HRM practices enable improved operational performance and bring other benefits, including increased employee satisfaction, to the company. However, contemporary management science does not provide an answer to whether effective HRM practices are universally applicable or should be tailored to an organization and its characteristics. The empirical study included small tourism enterprises in Mallorca. The aim of the study was to assess the impact of the scope and intensity of HRM formalization on the firms surveyed. A combined quantitative and qualitative approach was used. The level of HRM formalization among the surveyed companies varied, mostly being moderate. Increased employee motivation and perceived benefits depended on interacting factors, including sector and company size. The findings indicate that a significant factor in the success of formalization is the lack of a gap between planned and actual HRM policies, as well as proper communication and a supportive attitude from managers..